(5x+10=)

Simple and best practice solution for (5x+10=) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x+10=) equation:



(5x+10=)
We move all terms to the left:
(5x+10-())=0
We calculate terms in parentheses: +(5x+10-()), so:
5x+10-()
We add all the numbers together, and all the variables
5x
Back to the equation:
+(5x)
x=0/5
x=0

See similar equations:

| 2x-5(2x-4)=3(4-2x) | | 4x-10=23x+1 | | E)4x+1–9x=106 | | -1=3v-(8v-2) | | 18b+6=8b+20 | | -18v+2=-88 | | 17x+5=15+17x-2 | | -11=w/9 | | 6f=-9+3f | | 4x+16+6x+4=90 | | 7=-2-3r | | 142=(x+2)+x | | 2(x+6)=5(x-4) | | A1=5;d=2 | | 9.3g−6.08+6.3g=–11.05+14.9g | | 9x+6=(-12) | | 12x-10=7x | | 24-2x=4-12x | | -5y+3(y-6)=-24 | | 1.8f+6=2.8f=+8 | | -9.82+14.3q-8.27=12.72+18.2q | | 127+96+79+x=360 | | 16x-7=11x-25 | | 24-2x=4-12× | | 3c+20c+1=-20+2c | | 2(3x+4)+3=10x-9 | | –9j+9j=0 | | 5-3v-2v=-2v-7 | | -4(n-8)=2(6-7n) | | -4=-3u-3u-4 | | 7x-1+48=131 | | F(x)=-9x; |

Equations solver categories